(untitled) (Journal of Education and Development, 2022)
Since the Department for Education and Employment (DfEE) introduced the performance management system in general education in September 2000, it has become an important component in education reform in England. The goal of this study is to explore the challenges that teachers and principals may encounter in adopting performance management in educational leadership in England. This study finds that performance management provides a single, unfair mechanism for teacher evaluation, and within this framework, teachers’ personal development is largely ignored. And for leaders, performance management results in a lack of leadership responsibility. This study argues that performance management is not conducive to the development of schools in England.